An analysis of the impact of Media coverage on Earnings management in China - li, xingyue (2020)
There appears to be accounting fraud news is increasing in China. The phenomenon of earnings management is widespread in companies, which is widely discussed in literature nowadays. We consider combining internal and external governance to conduct research and explore new ways to curb earnings management more effectively. In this paper, we use China Shanghai and Shenzhen A shares of listed companies from 2009 to 2019 as the research object, using bidirectional fixed effects regression to study the relationship between media coverage and earnings management and how internal control quality moderates the above relation. The results indicate that the negative media coverage can effectively inhibit the behaviour of listed companies of accrual-based earnings management and internal control exerts a moderation effect on the relationship between media coverage and earnings management. This study provides additional insights into solving earnings management problems by exploring the role of media as external corporate governance and moderating effect of internal control as internal corporate governance, particularly from the perspective of an emerging market.